An Investigation Into The Relationships Between Creativity, Problem Solving And Life Stress: A Focus On Malaysian University Students - Tan, Chee Seng (2009)
Two studies were conducted to investigate the relationships between creativity, problem-solving ability and life stress. Dua siri penyelidikan telah dijalankan untuk meneliti hubungankait antara kreativiti, kebolehan menyelesaikan masalah dan tekanan hidup